О свободных неосесимметричных колебаниях полых пьезокерамических цилиндров конечной длины с радиальной поляризацией - Григоренко, А.Я.; Лоза, И.А. (Прикладная механика, 2010)
A problem on natural non-axisymmetrical vibrations of hollow piezoceramic cylinders with radial polarization is considered. To solve this problem, the effective numerical-analytical method is proposed. The initial three-dimensional problem of the theory of
electroelasticity is reduced to the twodimensional one by use of representation of vector
displacement components in the form of standing waves in the circumferential direction. Using the method of spline-collocations in the direction of axial coordinate, the two- dimensional problem in hand is reduced to the boundary value problem in direction of radial coordinate. The last problem is solved by the stable method of discrete orthogonalization together with the step-by-step method. The results of numerical analysis of frequencies of natural vibrations in the wide range of changing the geometrical characteristics of piezoceramic cylinders are given. Pозглянуто тривимірну задачу про власні неосесиметричні коливання порожнистих п’єзокерамічних циліндрів з осьовою поляризацією. Запропоновано ефективний чисельно-аналітичний метод для розв’язання крайових задач. Початкова тривимірна задача теорії електропружності в частинних похідних зводиться до двовимірної шляхом представлення компонент вектора переміщень у вигляді стоячих хвиль в коловому напрямі. Використовуючи метод сплайн-колокацій в напрямку осьової координати, вказана двовимірна задача зведена до крайової задачі на власні значення в напрямку радіальної координати, яка розв’язується стійким методом дискретної ортогоналізації у поєднанні з методом покрокового пошуку. Наведені результати чисельного аналізу частот власних коливань в широкому діапазоні зміни геометричних характеристик п’єзокерамічних циліндрів.